2009
DOI: 10.1002/ccd.22247
|View full text |Cite
|
Sign up to set email alerts
|

Economic analysis of angiography and preemptive angioplasty to prevent hemodialysis‐access thrombosis

Abstract: Objectives: We sought to determine the economic value of early angiography and prophylactic angioplasty to prevent hemodialysis‐access thrombosis. Background: End stage renal disease consumes more than 6% of the Medicare budget. There is a need to understand the financial impact of each component of care. Methods: We conducted an observational economic analysis of a closed cohort of 818 hemodialysis patients, of whom 560 were referred for 1437 consecutive radiographic procedures during an 8‐year period. Patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
24
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 19 publications
1
24
0
Order By: Relevance
“…Beathard (53) reported 6-month patency rates of 61% and 1-year patency rate of 38% after a variety of catheter interventions by interventional nephrologists. Several studies (39,54) have shown that autogenous arteriovenous fistulas tend to have longer median patencies than prosthetic grafts after catheter-based intervention (Fig. 12).…”
Section: Success Rates and Complicationsmentioning
confidence: 97%
“…Beathard (53) reported 6-month patency rates of 61% and 1-year patency rate of 38% after a variety of catheter interventions by interventional nephrologists. Several studies (39,54) have shown that autogenous arteriovenous fistulas tend to have longer median patencies than prosthetic grafts after catheter-based intervention (Fig. 12).…”
Section: Success Rates and Complicationsmentioning
confidence: 97%
“…Abandonment of a primary access frequently necessitates the creation of secondary and even tertiary accesses. The need for additional interventions 7) in a group of patients already immunocompromised by renal disease results in increased hospital stays, increased economic costs, 8) and increased morbidity and mortality. 1) Thus, it is important for nephrologists and vascular surgeons to adopt strategies that will minimize morbidity and maximize quality of life when dealing with patients on hemodialysis.…”
Section: Discussionmentioning
confidence: 99%
“…Bittl et al (12) recently published an economic analysis concluding that preemptive angiographic management of AVF dysfunction may represent a less efficient use of healthcare resources than increasing the number of patients with AVF. In the study presented here, we have demonstrated that salvage of clotted AVF by percutaneous thrombectomy rather than waiting for a new mature AVF, was associated with a reduction in access-related costs (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, maintenance of a previously thrombosed AVF could be a highly expensive policy. Published data regarding the economic value of vascular access surveillance and prophylactic angioplasty to prevent AVF thrombosis are controversial (12,13), and information about the cost-effectiveness of AVF salvage procedures has been limited.…”
mentioning
confidence: 99%